A study on the buckling behavior of in-service large open-topped oil-storage tanks. (February 2021) - Pan, Jianhua; Liang, Shenglin
Abstract: Oil storage tank is a typical thin-walled structure which is prone to buckling under external load. In this paper, the buckling behavior of the in-service open-topped oil-storage tank under wind loads is studied by analyzing four large in-service oil-storage tanks of 50000–150000 cubic meters. First, the general buckling behavior of oil-storage tanks under the external pressure without reinforcement device is analyzed by linear buckling. And the calculation accuracy of three calculation formulas for the critical buckling load of the storage tanks under uniform pressure is compared. Then the nonlinear buckling analysis is carried out by using the arc-length method, and the results show that the imperfection of the classical buckling mode has a significant influence on the buckling behavior of the storage tanks without reinforcement device. Finally, this paper focuses on the influence of wind girder and other reinforcement device on the buckling behavior of the tank, as well as the strengthening mechanism of the stored liquid on the in-service oil-storage tank. The results show that the reinforcement device affects the buckling behavior of the oil-storage tank by strengthening the stiffness of the tank top, while the stored liquid increases the stiffness of the tank bottom. Compared with the oil-storage tank without reinforcement device, the reinforcement effect of liquid on an oil tank equipped with a reinforcement device is more significant.